Engineering phase and density of Bose–Einstein condensates in curved waveguides with toroidal topology - Yelyzaveta Nikolaieva; Luca Salasnich; Alexander Yakimenko (New Journal of Physics, 2023)
We investigate the effects of ellipticity-induced curvature on atomic Bose–Einstein condensates confined in quasi-one-dimensional closed-loop waveguides. Our theoretical study reveals intriguing phenomena arising from the interplay between curvature and interactions. Density modulations are observed in regions of high curvature, but these modulations are suppressed by strong repulsive interactions. Additionally, we observe phase accumulation in regions with the lowest curvature when the waveguide with superflow has high eccentricity. Furthermore, waveguides hosting vortices exhibit dynamic transformations between states with different angular momenta. These findings provide insights into the behavior of atomic condensates in curved waveguides, with implications for fundamental physics and quantum technologies. The interplay between curvature and interactions offers opportunities for exploring novel quantum phenomena and engineering quantum states in confined geometries.